Spatial Pattern of Aid Allocation at the Regional Level: Evidence from 38 Sub-Saharan African Countries - Shon, Huijoo; Lee, HeeRae; Kim, Booyuel (KDI School of Public Policy and Management, 2022)
This study aims to analyze the geographical patterns of aid in the 21st century for 38 countries in sub-Sahara Africa and to identify the spatial exclusion of aid at the regional level. We calculated the spatial exclusion level (SEL) of aid by comparing the multidimensional poverty index (MPI) and aid spend, considering different sectors; health, education, and water & sanitation. Geocoded data from International Aid Transparency Initiative (IATI) was utilized and the number of projects is roughly 250,000. We found that the regions with higher MPI received less aid, leading to high spatial exclusion levels (SEL). Then, we identified that regions with similar SELs tend to cluster. Also, aid concentrated in regions that have urban properties or high accessibility. This spatial inequality of aid has intensified over time. The findings emphasize the need to target the appropriate sector of aid in consideration of spatial exclusion and regional geography.